KEPUASAN WISATAWAN TERHADAP KUALITAS PELAYANAN TOURIST INFORMATION COUNTERS DI JALAN PADMA UTARA LEGIAN, KUTA - I Gusti Ayu Eka Suwintari (Jurnal Ilmiah Hospitality Management, 2012)
The aim of this research are: 1) to know the level of tourists satisfaction toward the quality service of tourist information counters (TICs) at Padma Utara street, Legian, Kuta, 2) to know the influence of the factors regarding tourist satisfaction to improve the quality service of TICs at Padma Utara street, Legian, Kuta.  The observed factors are tangibility (F1) through four variables, reliability (F2) through three variables, responsiveness (F3) through six variables, assurance (F4) through four variables, and empathy (F5) through three variables.            This research was conducted in TICs at Padma Utara street, Legian, Kuta. In this research, there were 100 respondents selected as a sample using accidental sampling method. Data was collected by using questioners distributed to the tourists who were trying the product in TICs. The collected data was analyzed by confirmatory factor analysis with SPSS program version 19.0.            The research findings are: 1) the level of tourists’ satisfaction toward the quality service is generally satisfied enough, 2) the five factors in this research have their own influence towards tourist’s satisfaction on tourist satisfaction, in which the empathy factor is the most influencing factor toward guest satisfaction and reliability factor is improved. Based on the research findings, it is suggested that the TICs management needs to improve their quality service of the staff and the understanding of the characteristic of the tourists. The TICs is not only counter and communication facilities (tangible), but there are other element factors influence tourist satisfaction, such as attitude and personality of the staff when serving the tourists like knowing the customers’ name and smiling when serving them.